Manajemen Praktik Kerja Lapangan Dengan Dunia Usaha Dan Dunia Indutri Di SMK Darussalam Martapura - Sa'idah, Siti; Hermina, Dina (CV. Ulil Albab Corp, 2025)
The management of Field Work Practices (Praktik Kerja Lapangan, PKL) is a critical element in fostering effective collaboration between vocational high schools and the Business and Industrial Sectors (DU/DI). This study aims to explore the PKL management strategies at SMK Darussalam Martapura in strengthening collaboration with DU/DI while ensuring curriculum relevance to labor market needs. Using a qualitative descriptive approach, the study focuses on three key aspects: planning, implementation, and evaluation of PKL. The planning stage involves mapping industry needs, signing partnership agreements, and pre-PKL training. The implementation includes student placement in DU/DI, regular monitoring by supervising teachers, and maintaining student daily journals. Evaluation is carried out through feedback from DU/DI, which is used to revise the curriculum and enhance cooperation. The findings indicate that employing adaptive strategies, intensive communication, and leveraging technology in PKL management can address challenges such as limited industrial partners and differing expectations. These strategies have proven effective in enhancing student competencies and strengthening the relationship between SMK and DU/DI. This study recommends adopting similar strategies in other vocational institutions to strengthen the integration between education and industry demands.